Solid Nanomedicines of Nifurtimox and Benznidazole for the Oral Treatment of Chagas Disease - Miriam Rolon; Eustine Hanna; Celeste Vega; Cathia Coronel; Maria Auxiliadora Dea-Ayuela; Dolores R. Serrano; Aikaterini Lalatsa (MDPI AG, 2022)
Chagas disease (CD) is a parasitic zoonosis endemic in Central and South America affecting nearly 10 million people, with 100 million people at high risk of contracting the disease. Treatment is only effective when received at the early stages of the disease and it involved two drugs (nifurtimox (NFX) and benznidazole (BNZ)). Both treatments require multiple daily administrations of high doses, suffer from variable efficacy and insufficient efficacy in chronic CD, many side effects, and a very long duration of treatment that results in poor compliance, while combined available therapies that lead to reduced duration of treatment are not available and polypharmacy reduces compliance and increases the cost further. Here we present self-nanoemulsified drug delivery systems (SNEDDS) able to produce easily scalable combined formulations of NFX and BNZ that can allow for tailoring of the dose and can be easily converted to oral solid dosage form by impregnation on mesoporous silica particles. SNEDDS demonstrated an enhanced solubilisation capacity for both drugs as demonstrated by flow-through studies and in vitro lipolysis studies. High loading of SNEDDS to Syloid 244 and 3050 silicas (2:1 w/w) allowed clinically translatable amounts of both NFX and BNZ to be loaded. Tablets prepared from NFX-BNZ combined SNEDDS loaded on Syloid 3050 silicas demonstration near complete dissolution in the flow through cell apparatus compared to NFX and BNZ commercial tablets respectively (Lampit® and Rochagan®). NFX-BNZ-SNEDDS demonstrated nanomolar efficacy in epimastigotes and amastigotes of T. cruzi with acceptable selectivity indexes and demonstrated enhanced survival and reduced parasitaemia in acute murine experimental models of CD. Thus, the results presented here illustrate the ability for an easily scalable and personalised combination oral therapy prepared from GRAS excipients, enabling treatment access worldwide for the treatment of CD.